Online Booking Application for Wedding Photo Services (Case Study: Agan Photography) Based on Android - Putra Dadang Puryanto; Mohammad Suryawinata (Universitas Muhammadiyah Sidoarjo, 2021)
In the business world is now experiencing rapid development. One of them is the business of photography services is now much in demand by various circles, including in the field of wedding photo services business. Now many people do not want to just miss the wedding, and want to capture the moment of marriage. Therefore, a wedding photo service is now much in demand by some circles. One of the photo services in Sidoarjo now for example is Agan Photography. With increasingly advanced technology, ordering can be done online, therefore online booking application can be a solution and facilitate from both parties, both from customers or from the owner of the wedding photo service itself. This app aims to facilitate customers booking online and facilitate the payment of wedding photo services. The owner of photography services can also manage customer bookings in this application. This app uses android based smartphone which almost all circles have it.